Nanocrystal-Loaded Micelles for the Enhanced In Vivo Circulation of Docetaxel - Meng Cheng; Qiaoming Liu; Tiantian Gan; Yuanying Fang; Pengfei Yue; Yongbing Sun; Yi Jin; Jianfang Feng; Liangxing Tu (Molecules, 2021)
Prolonging in vivo circulation has proved to be an efficient route for enhancing the therapeutic effect of rapidly metabolized drugs. In this study, we aimed to construct a nanocrystal-loaded micelles delivery system to enhance the blood circulation of docetaxel (DOC). We employed high-pressure homogenization to prepare docetaxel nanocrystals (DOC(Nc)), and then produced docetaxel nanocrystal-loaded micelles (DOC(Nc)@mPEG-PLA) by a thin-film hydration method. The particle sizes of optimized DOC(Nc), docetaxel micelles (DOC@mPEG-PLA), and DOC(Nc)@mPEG-PLA were 168.4, 36.3, and 72.5 nm, respectively. The crystallinity of docetaxel was decreased after transforming it into nanocrystals, and the crystalline state of docetaxel in micelles was amorphous. The constructed DOC(Nc)@mPEG-PLA showed good stability as its particle size showed no significant change in 7 days. Despite their rapid dissolution, docetaxel nanocrystals exhibited higher bioavailability. The micelles prolonged the retention time of docetaxel in the circulation system of rats, and DOC(Nc)@mPEG-PLA exhibited the highest retention time and bioavailability. These results reveal that constructing nanocrystal-loaded micelles may be a promising way to enhance the in vivo circulation and bioavailability of rapidly metabolized drugs such as docetaxel.